Multiple effects of forced cooling on joint quality in coolant-assisted friction stir welding - X.C. Liu; W.T. Li; Y.Q. Zhou; Y.Z. Li; X.J. Pei; Z.K. Shen; Q.H. Wang (Journal of Materials Research and Technology, 2023)
To understand the multiple effects of forced cooling on the joint quality in coolant-assisted friction stir welding and the underlying mechanism, commercial pure aluminum AA1050 was welded by liquid–CO2–assisted friction stir welding (FSW) within a large process parameter range. The cooling effects on the weld formation, microstructure, and mechanical properties were investigated by comparison with conventional FSW. The microstructure evolution during the liquid–CO2–assisted FSW process was revealed by EBSD characterization together with thermal cycle measurement and short-time annealing. The results show that the process parameter window was narrowed by the liquid CO2 cooling. Forced cooling led to weld surface grooves and interior cavities under “too cold” welding conditions. The grains in the weld zone were refined and the areas of the weld cross-section were reduced by the forced cooling, resulting in the tensile strength of the joint being improved but the elongation being reduced. The thermal cycle shows that the liquid CO2 cooling compressed the welding temperature field by decreasing the heating rate and increasing the cooling rate, giving rise to the decrease in deformation temperature at the stirring stage. The low deformation temperature promotes dynamic recrystallization by changing the way of recrystallization and thus refines the grains. Further, the liquid CO2 cooling suppresses the grain growth which should have happened in natural cooling. Combining the above two aspects, the grain in the weld zone was refined and the tensile properties of the joints were changed. Nevertheless, the contribution of decreasing the deformation temperature to the grain refinement is more significant than that of increasing the cooling rate.